The Cysteinome of Protein Kinases as a Target in Drug Development. Issue 16 (2nd February 2018) - Chaikuad, Apirat; Koch, Pierre; Laufer, Stefan A.; Knapp, Stefan
Abstract: Drugs that function through covalent bond formation represent a considerable fraction of our repository of effective medicines but safety concerns and the complexity of developing covalent inhibitors has rendered covalent targeting a less attractive strategy for rational drug design. The recent approval of four covalent kinase inhibitors and the development of highly potent covalent kinase probes with exceptional selectivity has raised significant interest in industry and academic research and validated the concept of covalent kinase targeting for clinical applications. The abundance of cysteines at diverse positions in and around the kinase active site suggests that a large fraction of kinases can be targeted by covalent inhibitors. Herein, we review recent developments of this rapidly growing area in kinase drug development and highlight the unique opportunities and challenges of this strategy. Abstract : Hold on tight : Covalent inhibition of protein kinases has led to inhibitors with exceptional selectivity and potency. The recent FDA approval of four such kinase inhibitors has spurred considerable interest in this targeting strategy, which offers unique opportunities but also new challenges for drug development.